THE INFLUENCE OF LEADERSHIP FUNCTION, MOTIVATION AND ORGANIZATITON COMMITMEN TO JOB SATISFACTION TO CIVIL SERVANTS RELIGION MINISTER KERINCI REGENCY - Sukardi Sukardi; Marwan Usman (Program Studi Magister Manajemen, 2014)
The research is proposed to test the influence of leadeship function, motivation and organization comitment to job satisfaction to civil servants religion minister Kerinci regency. The population in this research wereto civil servants religion minister Kerinci regency.Then elected a sample size of 53to civil servants religion minister Kerinci regency with sample tecnique is used namely Total Sampling. The data which namely primer data and skunder data used in this research. For analyzing data by using path analysis and research hipothesis by using testing t with SPSS version 20 is used to analyze the data. The analyze result shows that the leadeship function to cause the positve and significantmotivation also to cause the positve and significant organization commitmen. The analyze result also shows that the leadeship function and motivation to cause the positive and significant to job satisfactionand organization comitmenthas no contribution to job satisfaction. Keywords : Leadeship Function, Motivation and Organization Comitment to Job Satisfaction